HADIS MAUDHU’I: KEKHALIFAHAN DALAM PEMERINTAHAN ISLAM PERSPEKTIF HADIS - Fakhriza, Haris; Hudaya, Hairul (Institut PTIQ Jakarta, 2024)
The Caliphate as an Islamic-based government system has colored the history of Islamic world civilization for centuries. Since the life of the Prophet Saw until the era of Khulafaur Rashidin's reign. However, the discourse about its relevance and implementation in government is often colored by debates about the pros and cons, one of which is related to the existence of maudhu'i (thematic) hadiths that support or even discredit the Khilafah system. This research aims to examine the Maudhu'i (thematic) hadith of the Khilafah in the Islamic government discourse from a hadith perspective. The research methodology uses a qualitative approach with analysis of hadith texts and related literature. Research findings show that the existence of maudhu'i (thematic) hadith has sparked controversy and confusion in understanding the concept and model of the ideal Khilafah. Maudhu'i (thematic) hadiths supporting the Khilafah are often used by certain groups to legitimize claims of absolute authority and certain government structures. On the other hand, Maudhu'i hadiths which discredit the Khilafah are used by other parties to reject this model of government as a whole. This research concludes that to build a contextual and relevant Khilafah discourse in the modern era, critical awareness of the existence of the Maudhu'i hadith is needed. Tracing the sanad (chain of narration) and holistic analysis of the contents of hadith are crucial in selecting sources that are valid and reflect authentic Islamic teachings. In addition, it needs to be understood that the Khilafah is not a single and indisputable model, but rather a concept that must be adapted and interpreted according to the socio-political dynamics and needs of Muslims in the contemporary era